Evaluation of a midwifery initiated oral health-dental service program to improve oral health and birth outcomes for pregnant women: A multi-centre randomised controlled trial. (June 2018) - George, Ajesh; Dahlen, Hannah G.; Blinkhorn, Anthony; Ajwani, Shilpi; Bhole, Sameer; Ellis, Sharon; Yeo, Anthony; Elcombe, Emma; Johnson, Maree
Abstract: Background: Oral health care during pregnancy is important for the health of the mother and child. However, pregnant women have limited knowledge about maternal oral health and seldom seek dental care. Further, due to limited training antenatal care providers like midwives rarely discuss oral health with pregnant women. The Midwifery-Initiated Oral Health Dental Service program was developed to address current gaps in oral promotional interventions during pregnancy. Objectives: To assess the effectiveness of a Midwifery-Initiated Oral Health Dental Service program in improving uptake of dental services, oral health knowledge, quality of oral health, oral health status and birth outcomes of pregnant women. Design: Multi-centre randomised controlled trial. Setting: Three large metropolitan public hospitals in Sydney, Australia. Participants: Pregnant women attending their first antenatal appointment who were at least 18 years old and had a single low risk pregnancy between 12 and 20 weeks gestation. Methods: 638 pregnant women were allocated to three groups using block randomisation (n = 211) control group, intervention group 1 (n = 215), intervention group 2 (n = 212) and followed up till birth. Study investigators and data collectors were blinded to group allocation. Intervention group 1 received a midwifery intervention from trained midwives involving oral health education, screening and referrals to existing dental pathways. Intervention group 2 received the midwifery intervention and a dental intervention involving assessment/treatment from cost free local dental services. The control group received oral health information at recruitment. Primary outcome was uptake of dental services. Secondary outcomes included oral health knowledge, quality of oral health, oral health status and birth outcomes. Results: Substantial improvements in the use of dental services (20.2% Control Group; 28.3% Intervention group 1; 87.2% Intervention group 2; Odds Ratio Intervention group 2 vs Control Group = 29.72, 95% CI 15.02–58.53, p < 0.001), women's oral health knowledge (p = 0.03); quality of oral health (p < 0.001) and oral health outcomes (sulcus bleeding, dental plaque, clinical attachment loss, decayed/filled teeth- p < 0.001) were found in Intervention group 2. No difference in the rate of preterm or low-birth weight was found. Conclusions: The Midwifery-Initiated Oral Health Dental Service program (Intervention group 2) improved the uptake of dental services and oral health of pregnant women and is recommended during antenatal care. A cause and effect relationship between this intervention and improved birth outcomes was not supported.